Удаан M^{-}+He мөргөлдөөний үед электроны корреляц тооцох асуудал - Х, Цоохүү; Н, Цогбадрах (Scientific transaction of the National University of Mongolia. Physics, 2022)
An adiabatic electronic wave function for helium atoms depending on distance between the heavy particles (the negative meson and the target nuclear) is constructed. Both the radial and angle correlations are included in the wave function and the adiabatic electronic term for the He(1s2)+M- system is calculated. It is shown that the adiabatic electronic term for the elastic (M-+He(1s2) ) and ionization (M-+He(1s)) channels cross twice at the distance R1=0.88a0 and R2=0.215a0 between heavy particles. A possible corrections to the theory for ionization of atoms by slow meson impact, due to the second crossing point (R2), are discussed.